2014
DOI: 10.1371/journal.ppat.1004029
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into How Yersinia pestis Adapts to Its Mammalian Host during Bubonic Plague

Abstract: Bubonic plague (a fatal, flea-transmitted disease) remains an international public health concern. Although our understanding of the pathogenesis of bubonic plague has improved significantly over the last few decades, researchers have still not been able to define the complete set of Y. pestis genes needed for disease or to characterize the mechanisms that enable infection. Here, we generated a library of Y. pestis mutants, each lacking one or more of the genes previously identified as being up-regulated in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 57 publications
2
61
1
Order By: Relevance
“…We suggested previously that hicB3 may be involved in plague pathogenesis (3). Our present results show that a Y. pestis ⌬hicA3B3 mutant is fully virulent; hence, the loss of virulence of the ⌬hicB3 mutant is due to inefficient in vivo growth caused by the activity of free HicA3 RNase, not to the lack of HicB3 as a regulator.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…We suggested previously that hicB3 may be involved in plague pathogenesis (3). Our present results show that a Y. pestis ⌬hicA3B3 mutant is fully virulent; hence, the loss of virulence of the ⌬hicB3 mutant is due to inefficient in vivo growth caused by the activity of free HicA3 RNase, not to the lack of HicB3 as a regulator.…”
Section: Discussionsupporting
confidence: 53%
“…We reported previously that Y. pestis lacking ypo3369 is attenuated for virulence (3). ypo3369 is referred to as hicB3 by another research group, since its 135-aa product presents homology with the HicB antitoxin in the Escherichia coli HicA-HicB TAS (5).…”
Section: Hica3-hicb3 Is a New Tas In Y Pestismentioning
confidence: 99%
See 2 more Smart Citations
“…While the loss of Prdx6 results in increased ROS production during ALI/ARD, during infection with Y. pestis, the bacterial Yop-Ysc type III secretion system might otherwise serve as a mechanism to suppress ROS generation within the host, even in the absence of Prdx6. Based on gene expression data collected from rat buboes and infected macrophages, it has been shown that Y. pestis encounters ROS during the initial stage of infection but not later (58). Therefore, it remains possible that the cleavage of Prdx6 may affect the infection in ways not assessed here or that the impact may be masked by the activities of other Y. pestis virulence factors.…”
Section: Discussionmentioning
confidence: 93%